Mutual coupling between submicrostrip grid arrays on electrically thin substrate - Chen, Zihao (2019)
This communication presents a study of mutual coupling between submicrostrip grid arrays on electrically thin substrate. It is found that the mutual coupling between subgrid arrays on electronically thin substrate is mainly caused by dielectric polarization currents. High isolation between subgrid arrays can be achieved by proper selection of the antenna array factor and size. A particular example of microstrip grid array antenna with five subarrays is developed on RT/duroid 5880 substrate for simultaneous transmit and receive application with high measured isolation of 65.07 dB at 24.15 GHz between transmitting and receiving antennas.